eGFR Evalutation among the Hypothyroid Patients Attending at a Tertiary Center of Chattogram (IAHS Medical Journal, 2024)
Background: Hypothyroidism is a prevalent endocrine illness that affects people all over the world. The modulation of renal hemodynamics and basal metabolic rate is disrupted in hypothyroidism. The kidney is generally involved in thyroid hormone metabolism, breakdown and excretion. Chronic renal hypoperfusion affects the hypothalamic pituitary-thyroid axis, resulting in low circulating thyroid hormone levels, changed peripheral hormone metabolism, decreased tissue thyroid hormone content and altered thyroid iodine storage. Recent research has linked an increased risk of hypothyroidism to a decreased estimated Glomerular Filtration Rate (eGFR). The purpose of the study is to determine the association between eGFR with hypothyroidism in a tertiary care hospital of Chattogram.Materials and methods: A cross-sectional study was done during July 2022 to June 2023 including 100 diagnosed hypothyroidism cases attending in Chittagong Medical College Hospital. Serum Thyroid Stimulating Hormone (TSH) serum free thyroxine (FT4) serum creatinine, and blood urea were measured. The estimated glomerular filtration rate (eGFR) were determined. The result were analysed using SPSS version 25.Results: The mean age was 42.76±10.18 years with 93% female. Most of the patients (92%) were in a subclinical hypothyroid state and 8% were in an overt hypothyroid state. The mean ±SD serum creatinine levels and urea levels were 0.8±0.2mg/dl and 25.4±6.5 mg/dl, respectively. The mean eGFR was 75.36±7.54 ml/min/1.73 m2. There was a significant decrease in mean eGFR in the < 60 ml/min/1.73m2 group among the study population. There was a significant association between decreased eGFR and hypothyroidism. Serum TSH had significantly shown a negative correlation with eGFR. Serum TSH level had a significant positive correlation with serum creatinine (r=0.56, p